Design of a New Robot for Working in Building Environment - 臧红彬; 陶俊杰; 周颖玥; 许雄; 蔡勇; 沈连婠 (Jixie chuandong)
A new robot is designed which has three degrees of freedom movement in the round plane and can passively cross the vertical barriers up to 2. 5 times radius of the wheel. The six drive wheels control are used in this robot,four Mecanum wheels with a rectangular arrangement are used in its body to make it have a omni- directional motion function in plane ground. The front and rear wheels of the robot uses omni- directional wheels,so that it can keep rolling state with the ground when cornering and lateral movement. The six wheels are mounted on an elevated body such as climbing linkage mechanism,climb mechanism,stable mechanism,,so it has a good stair climbing and obstacle functions. The general kinematics model of the omni- directional motion system is given,and the necessary condition for the realization of the omni- directional motion is the inverse of the Jacobi matrix with full rank. The structure and layout of the wheels for the omni- directional motion system is optimized and selected. The functions of the robot system including straight movement,lateral movement,zero turning radius and climbing the stairs are simulated based on the virtual prototype technology.